FAMILY EDUCATION VALUES IN KIRANA KEJORA’S NOVELS (GENETIC STRUCTURAL RESEARCH) - Wulan Wahyuning Ratri; . Emzir; Ninuk Lustyantie (University of Kuningan, 2017)
The objective of this research is to acquire deep understanding about family education values in the novels by Kirana Kejora through genetic structural. It was a qualitative research with content analysis method. This research was analyzed through structural literary approach and genetic structural approach. The data were collected through document study, data observation about family education values in the novels by Kirana Kejora (Bintang Anak Tuhan, Air Mata Terakhir Bunda, Ayah Menyayangi Tanpa Akhir), and interview with Kirana Kejora. The result of this research revealed that family education values that were founded and described in the novels by Kirana Kejora were diligent to worship, honest, respect, unanimous, having achievement, mandate, brave, independent, proportional, take care of self, affection, prelude other people, and fair. They were founded and described through intrinsic structure of novel, author’s background, social background, and author’s world view. Those results lead to implication that Indonesian literature educator can use Kirana Kejora’s novels directly in the teaching process. Further, the findings lead to recommendation to Indonesian literature educators in order to use novels with content of family education values and to motivate students to analyze the novels through genetic structural.Keywords: family education values, novel, genetic structural